Amphipathic guanidine-embedded glyoxamide-based peptidomimetics as novel antibacterial agents and biofilm disruptors. Issue 9 (16th February 2017) - Nizalapur, Shashidhar; Kimyon, Onder; Yee, Eugene; Ho, Kitty; Berry, Thomas; Manefield, Mike; Cranfield, Charles G.; Willcox, Mark; Black, David StC; Kumar, Naresh
Abstract : Novel antibacterial peptidomimetics that inhibit the growth of planktonic cells and reduce biofilm formation in both Gram-positive and Gram-negative bacteria. Abstract : Antimicrobial resistance in bacteria is becoming increasingly prevalent, posing a critical challenge to global health. Bacterial biofilm formation is a common resistance mechanism that reduces the effectiveness of antibiotics. Thus, the development of compounds that can disrupt bacterial biofilms is a potential strategy to combat antimicrobial resistance. We report herein the synthesis of amphipathic guanidine-embedded glyoxamide-based peptidomimetics via ring-opening reactions of N -naphthoylisatins with amines and amino acids. These compounds were investigated for their antibacterial activity by the determination of minimum inhibitory concentration (MIC) against S. aureus and E. coli . Compounds35, 36, and66 exhibited MIC values of 6, 8 and 10 μg mL −1 against S. aureus, respectively, while compounds55 and56 showed MIC values of 17 and 19 μg mL −1 against E. coli, respectively. Biofilm disruption and inhibition activities were also evaluated against various Gram-positive and Gram-negative bacteria. The most active compound65 exhibited the greatest disruption of established biofilms by 65% in S. aureus, 61% in P. aeruginosa, and 60% in S. marcescens respectively, at 250 μM concentration, while compound52 inhibited the formation of biofilms by 72% in S. marcescens at 250 μM. We also report here the in vitro toxicity against MRC-5 human lung fibroblast cells. Finally, the pore forming capability of the three most potent compounds were tested using tethered bilayer lipid membrane (tBLM) technology.